IMPLEMENTASI SISTEM KASIR PINTAR BERBASIS WEB PADA UMKM SEBLAK REYHAN KAMPUNG MELAYU JAKARTA TIMUR - Aulia Maulida; Mesra Betty Yel; Rasiban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information technology currently has an important role in improving the effectiveness and efficiency of business management, especially for Micro, Small, and Medium Enterprises (MSMEs). The use of information technology not only assists in data processing but also supports faster, more accurate, and more structured services. Seblak Reyhan MSME, which operates in the culinary sector, still faces several obstacles in service processes and business management because the system used is still manual. The processes of recording transactions, managing stock, and preparing sales reports are considered less effective, time-consuming, and prone to data recording errors. This study aims to design and implement a Web-Based Smart Cashier System at Seblak Reyhan MSME, Kampung Melayu, East Jakarta, to assist in sales transactions, product data management, stock recording, and automatic report generation. The data collection methods used in this study were observation, interviews, and literature study. Meanwhile, the system development method used was the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The result of this study is a web-based smart cashier system capable of helping business owners and cashiers perform sales transactions more effectively and efficiently. The developed system can simplify product data management, accelerate transaction processes, reduce recording errors, and generate sales reports automatically and systematically. With the implementation of this system, it is expected to improve service quality and support better and more modern business management at Seblak Reyhan MSME.